The Indonesian stock market responded negatively to Trump: Impact of import tariff policies - Suhendra S; Edy Jumady; Marwah Yusuf (IECON: International Economics and Business Conference, 2025)
This study analyzes the impact of the United States' import tariff policy announcement on April 2, 2025, on stock price movements in the LQ-45 index on the Indonesia Stock Exchange. Using the Event Study method, this study compares stock prices and market volatility 30 days before and 30 days after the policy announcement. Data were obtained from the daily closing prices of LQ-45 stocks collected through purposive sampling. The analysis was conducted using paired t-tests and Wilcoxon Signed Rank tests to assess the significance of average price differences, as well as standard deviation calculations to evaluate changes in market volatility. The results indicate that there was an increase in the average LQ-45 index after the import tariff announcement, followed by a decrease in market volatility. However, this increase was not statistically significant (p-value > 0.05), suggesting that the policy's impact on LQ-45 stock prices is limited. These findings align with the Capital Market Efficiency Theory, where information is already reflected in stock prices before the announcement, as well as the Signal Theory, which emphasizes that the impact of global economic policies does not always result in extreme reactions in domestic markets. This study contributes to the literature on the response of the Indonesian stock market to international economic events and highlights the importance of psychological factors and anticipatory investor behavior. The main recommendation is the need for further research with a broader sample and variables, including the measurement of investor sentiment as a determinant of market reactions.